2002
DOI: 10.1172/jci0214873
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen alters thresholds for B cell apoptosis and activation

Abstract: Estrogen is thought to contribute to the increased frequency of autoimmune disorders occurring in females, but a molecular basis for its effects on autoimmunity remains to be elucidated. We have shown previously that estrogen leads to the survival and activation of autoreactive cells in the naive repertoire. To identify the molecular pathways involved in B cell tolerance, we sought to identify genes that are differentially regulated by estrogen in mouse B cells. Several genes involved in B cell activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
202
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(242 citation statements)
references
References 54 publications
15
202
4
Order By: Relevance
“…40 Considerable evidence supports the hypothesis that depressed levels of CD22 on B cells can promote IgG ANA production. [41][42][43] In contrast to our results, Grimaldi et al 44 found that mRNA and surface protein expression of Cd22 were upregulated in response to E2 in BALB/c mice and proposed that this upregulation may be involved in the escape of autoreactive B cells from tolerance. Differences in the dose of E2 used or the genetic background of the mice may have contributed to this discordance.…”
Section: Discussioncontrasting
confidence: 99%
“…40 Considerable evidence supports the hypothesis that depressed levels of CD22 on B cells can promote IgG ANA production. [41][42][43] In contrast to our results, Grimaldi et al 44 found that mRNA and surface protein expression of Cd22 were upregulated in response to E2 in BALB/c mice and proposed that this upregulation may be involved in the escape of autoreactive B cells from tolerance. Differences in the dose of E2 used or the genetic background of the mice may have contributed to this discordance.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, these data suggest that estrogens favor the development and/or exacerbation of the disease, while androgens seem to be protective (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Systemic Lupus Erythematosus (Sle) Is An Autoimmune Disease mentioning
confidence: 93%
“…Magnetic bead sorting for B220 þ cells is commonly used to purify B cells and does not directly result in their activation. [52][53][54] The major caveat to this second approach is that gene expression profiles obtained through this method would be representative of a mixed population of cells, not a single subset; however, by judiciously choosing the tissues to examine, we can highly enrich for specific cell populations.…”
Section: Resultsmentioning
confidence: 99%